Synthesis and evaluation of 3-hydroxy-3-phenylpropanoate ester–AZT conjugates as potential dual-action HIV-1 Integrase and Reverse Transcriptase inhibitors. Issue 24 (15th December 2015) - Manyeruke, Meloddy H.; Olomola, Temitope O.; Majumder, Swarup; Abrahams, Shaakira; Isaacs, Michelle; Mautsa, Nicodemus; Mosebi, Salerwe; Mnkandhla, Dumisani; Hewer, Raymond; Hoppe, Heinrich C.; Klein, Rosalyn; Kaye, Perry T.
Graphical abstract: 3-Hydroxy-3-phenylpropanoate ester–AZT conjugates have been prepared and their potential as dual-action HIV-1 Integrase and Reverse Transcriptase inhibitors has been explored and compared with their cinnamate ester analogues. Abstract: Novel 3-hydroxy-3-phenylpropanoate ester–azidothymidine (AZT) conjugates have been prepared using Baylis–Hillman methodology, and their potential as dual-action HIV-1 Integrase and Reverse Transcriptase inhibitors has been explored using enzyme inhibition and computer modelling techniques; their activity and HeLa cell toxicity have been compared with those of their cinnamate ester analogues.